Вае уломе валче: кырӟанъёс / Г. Н. Матвеев - Матвеев Геннадий Николаевич (Удмуртия, 1991)
Экземпляры: (20240507) / Инвентарный номер: 22179 / Цена: 144.00 / Сис.шифр: 85.3(2=664.1) / Авт.знак: М 33 / ГРНТИ: 18 / ББК: 85.3(2=664.1)